2017
DOI: 10.1038/ncomms14839
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and reactivity of a mononuclear non-haem cobalt(IV)-oxo complex

Abstract: Terminal cobalt(IV)–oxo (CoIV–O) species have been implicated as key intermediates in various cobalt-mediated oxidation reactions. Herein we report the photocatalytic generation of a mononuclear non-haem [(13-TMC)CoIV(O)]2+ (2) by irradiating [CoII(13-TMC)(CF3SO3)]+ (1) in the presence of [RuII(bpy)3]2+, Na2S2O8, and water as an oxygen source. The intermediate 2 was also obtained by reacting 1 with an artificial oxidant (that is, iodosylbenzene) and characterized by various spectroscopic techniques. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 59 publications
14
130
1
3
Order By: Relevance
“…Interestingly,t he reactive Co IV centerh as ah igh degree of radicalc haracter distributed over the CoÀOb ond. Such electronic structure fingerprints of high-valent Co moieties were recently shown to be related to reactivity, [43] where an apparent Co IV =oxo species having am ixed electronic structure of the oxyl/oxo type was reported. In that work, one of us (Y.D.)…”
Section: Electronicstructure Calculationssupporting
confidence: 75%
See 1 more Smart Citation
“…Interestingly,t he reactive Co IV centerh as ah igh degree of radicalc haracter distributed over the CoÀOb ond. Such electronic structure fingerprints of high-valent Co moieties were recently shown to be related to reactivity, [43] where an apparent Co IV =oxo species having am ixed electronic structure of the oxyl/oxo type was reported. In that work, one of us (Y.D.)…”
Section: Electronicstructure Calculationssupporting
confidence: 75%
“…In that work, one of us (Y.D.) showed that, similarly to the case reported here, the oxowall [43] was indeed not broken,a nd the local quartet spin arrangement, delocalized alongt he CoÀOb ond, showed substantial radicalc haracter on oxygen.O verall, am ore appropriate electronic structure assignment for the in situ generated, catalytically competent, OÀOb ond-formings pecies is am ixed Co-oxo/oxyl. CN stretching frequencies (n(CN)) and molecular orbitals were investigated to elucidate the molecular basis for the catalytic activity ( Table 2).…”
Section: Electronicstructure Calculationsmentioning
confidence: 99%
“…[58] Moreovert he bond order of around 1.6 indicates that the oxowall [58] wasindeed not broken,but there is as ubstantial radical character on the oxygen. The electrons in the bonding and antibonding set of orbitals 50, 53 and 51, 54 contribute to al arge radicalc haractero n oxygen, that is, approximatelyo ne electron.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, formal assignmentso fC o IV (O)o rC o III -(OC)f or the Co center are incom- Overall, these give ab ond order of (5.57-2.41)/2 = 1.58, suggesting as ignificant double bond character,y et still far from af ormal Co=oxo nature.R ecently,asimilar electronic structure fingerprint and its relation to reactivity for Co-oxo/oxyls ystemsw as demonstrated. [58] Moreovert he bond order of around 1.6 indicates that the oxowall [58] wasindeed not broken,but there is as ubstantial radical character on the oxygen. Hence, it can be surmised that high valenta nd reactive Co moieties share this mixed Co-oxo/oxyl feature, and we are in the process of generalizing this theoretically to an umber of catalytically active Co-oxo/oxylsystems.…”
Section: Resultsmentioning
confidence: 99%
“…[183] Likewise, monometallic and bimetallic Fe-, Ni-, Cu-, Co-, and Mn-cyclam complexes allow for OÀOb ond activation and formationo fh igh-valent metal-oxo species. [186][187][188][189][190] Among these complexes, the Co IV -oxo complexes in particular were shown to facilitate CÀHb ond activation, epoxidation of olefins, and oxygen transfer-reactions. [186]…”
Section: àmentioning
confidence: 99%